026 The all Ireland traveller birth cohort study: overcoming recruitment challenges to estimate birth parameters. (16th November 2010) - Hamid, N A; Abdalla, S; Turner, J; Quirke, B; Niccharthaigh, R; Kelleher, C; Fitzpatrick, P; ,
Abstract : Objective: Irish Travellers are a significant minority group characterised by a nomadic lifestyle, specific culture, and significant socio-economic and health disadvantage. When last documented in 1986, their fertility rate was one of the highest in Europe and infant mortality was almost 3 times the Irish average. The purpose of this study was to investigate prospectively the health status, health utilisation and health care needs of Traveller infants from birth through first year of life. Setting: The Traveller Birth Cohort Study is a linkage sub-study of the All Ireland Traveller Health Study (AITHS) on Island of Ireland (IOI): Republic of Ireland (ROI) and Northern Ireland (NI). Participants: All proband babies born to self-identifying Traveller mothers over a one year period (13 th October 2008 to 14 th October 2009) on IOI. Methodology: A two-stage recruitment process was undertaken through families themselves during the main census using an innovative audio-visual computer-based survey and subsequently consents for the study were obtained by the public health nurses (PHN) or the main study coordinator. In ROI, identification of participants was aided by birth notification forms, the national metabolic screening registers, PHNs' local knowledge and Traveller health projects, and in NI, by Health Visitor notifications and informal local Traveller networks. The participating mothers carry a specifically designed Parent-held Child Record. Fertility rates calculation used data from between the cohort and the AITHS census. Results: 980 eligible mothers were identified; to date 468 (51.2%) mothers consented in ROI and 34 (50.7%) in NI (in progress). Median maternal age was 25cyears old (mean 25.8, SD 5.6) compared to the 2007 national average of 31.1; with 75% of the cohort group under 30 years old. Peak age-group for Travellers was 20-24 years old, this was 30–34 years old for general population. 980 babies were identified, 14 were twins and 51.5% were male. Since 1986, the Travellers (ROI) crude birth rate has dropped from 34.9 to 25.1; the general- and total period- fertility rates have also dropped from 164.1 to 97.0 and from 5.3 to 2.9 respectively. Both are still significantly above the 2008 ROI national average of 64.6 and 2.1. 30.6% of Traveller births occurred in the 3 major Dublin maternity hospitals compared to the 35% of total national births in 2008. Conclusions: In a difficult-to-reach nomadic minority group this study has overcome significant challenges in recruitment. Data to date indicates a downward trend in birth rate in this group.